Impact of Financing Problems on Baitul Mal wa Tamwil during Covid-19 - Ma’watu Shalihah Kaily; Achmad Firdaus; Wahyu Dwi Agung Priyo Susila (Global Review of Islamic Economics and Business, 2023)
Abstract: This study evaluates the cause and effect of financing problems on Baitul Mal wa Tamwil (BMT) during COVID-19 and analyzes the strategy taken by BMT to handle financing problems. This study is qualitative research. The primary and secondary data were obtained from observations, interviews, and documentation. The informants of the study are top management and members of BMT Al Hidayah Kotaraja Lombok Timur. The data are analyzed using the FMEA (Failure Mode and Effect Analysis) approach. The FMEA method is a systematic method used to identify and prevent problems in a company's product or business process. All process is calculated in a score, namely Risk Priority Number (RPN), and shown in the Pareto diagram. Financing problems are categorized as substandard, doubtful, and bad financing. The causes of financing problems are, among others, the employee’s lack of ability to assess the personality of the prospective debtors in fulfilling their installments, and natural disasters (the COVID-19 pandemic) that may affect someone’s financial ability. Financing problems have an impact on the emergence of financing risk. BMT Al Hidayah Kotaraja is also directly impacted by the inefficient money flow because monthly profit sharing still needs to be distributed to the members. The main factor causing this problem is staff members' inability to evaluate potential debtors. Additionally, the company's approach to these financing problems has not been working. The management, in that case, focused on the debtors instead of their employee’s capability. In that circumstance, the management ought to focus on improving the capacity of their staff to evaluate potential members. According to this study's findings, the FMEA is applicable in resolving finance issues in BMT. Originality/Value: The research related to risk management in BMT, especially NPF caused by the COVID-19 pandemic, using the FMEA (Failure Mode and Effect Analysis) method. FMEA is a systematic method used to identify and prevent problems with a company's products or business processes from occurring. FMEA is used to examine risk management in banking and provides convenience to the management in making decisions for planning, maintenance, and development purposes. The FMEA method in this study identifies and prevents problems in BMT.